2010
DOI: 10.1038/ng.684
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide patterns of genetic variation among elite maize inbred lines

Abstract: We have resequenced a group of six elite maize inbred lines, including the parents of the most productive commercial hybrid in China. This effort uncovered more than 1,000,000 SNPs, 30,000 indel polymorphisms and 101 low-sequence-diversity chromosomal intervals in the maize genome. We also identified several hundred complete genes that show presence/absence variation among these resequenced lines. We discuss the potential roles of complementation of presence/absence variations and other deleterious mutations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
370
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 441 publications
(396 citation statements)
references
References 31 publications
25
370
0
1
Order By: Relevance
“…After quality control, we identified totally 3,619,762 SNPs using B73 as the reference by a two-step procedure with multiple criteria 11,12 (Table 1). Among them, 2,636,164 SNPs were in the exons, which is 5.6 times greater than that previously reported in a group of six elite maize inbred lines (468,900 exonic SNPs) 13 , 7.5 times higher than that reported in the nested association mapping (NAM) population (352,000 exonic SNPs) 14 and 35.7 times higher than that reported between B73 and Mo17 (73,900 exonic SNPs) 14 . Moreover, 69.7% of SNPs in the NAM population and 87.5% of SNPs in the B73/Mo17 were included in our SNP set (Fig.…”
mentioning
confidence: 55%
“…After quality control, we identified totally 3,619,762 SNPs using B73 as the reference by a two-step procedure with multiple criteria 11,12 (Table 1). Among them, 2,636,164 SNPs were in the exons, which is 5.6 times greater than that previously reported in a group of six elite maize inbred lines (468,900 exonic SNPs) 13 , 7.5 times higher than that reported in the nested association mapping (NAM) population (352,000 exonic SNPs) 14 and 35.7 times higher than that reported between B73 and Mo17 (73,900 exonic SNPs) 14 . Moreover, 69.7% of SNPs in the NAM population and 87.5% of SNPs in the B73/Mo17 were included in our SNP set (Fig.…”
mentioning
confidence: 55%
“…Taking advantage of recent resequencing results (27), we tested five genes from reciprocal crosses between inbreds Zheng58 and Chang7-2. Our results showed that all of the tested genes had the same imprinting effect in Zheng58 and Chang7-2 as in B73 and Mo17 (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Maize, in particular, has a high level of sequence and structural diversity (Buckler et al, 2006;Springer et al, 2009;Lai et al, 2010). A genomic comparison of two maize inbreds, B73 and Mo17, revealed an unprecedented level of genomic structural diversity compared with most higher eukaryotes studied thus far (Springer et al, 2009).…”
Section: Conventional Plant Breeding Sources Of Genetic Variation Usementioning
confidence: 99%